2022
DOI: 10.3389/fsurg.2021.663099
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Therapeutic Effects of PVP and PKP Combined With Triple Medication on Mild and Moderate Osteoporotic Vertebral Compression Fracture in the Elderly

Abstract: ObjectiveTo compare and analyze the therapeutic effect of percutaneous vertebroplasty (PVP) and percutaneous kyphoplasty (PKP) combined with triple therapy on elderly patients with mild to moderate osteoporotic vertebral compression fractures (OVCF).MethodsA total of 114 cases of elderly patients with mild to moderate osteoporotic vertebral compression fractures were identified as research subjects in our hospital from January 2017 to January 2018, and a total of 136 vertebrae were included. The patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Further high-quality multicenter randomized controlled tri-als with longer follow-up and larger sample sizes are needed, but at this time indicate that there are no significant differences between PVP and BKP in terms of VAS score, ODI score, or cement leakage, and that both are useful treatments for patients with OVF. [25][26][27][28][29][30][31][32][33][34] On the other hand, a systematic review comparing BKP and PVP, focusing on the primary outcome of height restoration and the secondary outcomes of pain relief and function (33 total randomized controlled trials; 20 BKP, 7 PVP, and 6 comparing PVP to BKP), suggested that BKP may be superior in restoring vertebral height, but both procedures restored some vertebral height reduction, kyphosis, Cobb angle, and wedge angle, and showed benefit in pain reduction and patient-reported functional improvement. However, it is not possible to definitively conclude whether BKP or PVP is superior in reducing pain and restoring function because many studies that examined all 3 variables did not report statistically significant results, and more definitive studies and data analysis are needed to confirm this finding (Figs.…”
Section: Which Is Better With Pvp Versus Bkp?mentioning
confidence: 99%
“…Further high-quality multicenter randomized controlled tri-als with longer follow-up and larger sample sizes are needed, but at this time indicate that there are no significant differences between PVP and BKP in terms of VAS score, ODI score, or cement leakage, and that both are useful treatments for patients with OVF. [25][26][27][28][29][30][31][32][33][34] On the other hand, a systematic review comparing BKP and PVP, focusing on the primary outcome of height restoration and the secondary outcomes of pain relief and function (33 total randomized controlled trials; 20 BKP, 7 PVP, and 6 comparing PVP to BKP), suggested that BKP may be superior in restoring vertebral height, but both procedures restored some vertebral height reduction, kyphosis, Cobb angle, and wedge angle, and showed benefit in pain reduction and patient-reported functional improvement. However, it is not possible to definitively conclude whether BKP or PVP is superior in reducing pain and restoring function because many studies that examined all 3 variables did not report statistically significant results, and more definitive studies and data analysis are needed to confirm this finding (Figs.…”
Section: Which Is Better With Pvp Versus Bkp?mentioning
confidence: 99%
“…[5][6][7][8] Percutaneous kyphoplasty (PKP) is a rapid, effective, and minimally invasive technique for treating TLOVFs in elderly patients, and it can speed recovery of function and improve quality of life with fewer complications compared with conservative treatment. [9][10][11][12][13] However, surgeons are heavily dependent on image-guided navigation, especially when the surgeon is inexperienced. The radiation dose of the operator was highest in C-arm-guided minimally invasive spine surgery.…”
Section: Introductionmentioning
confidence: 99%